THE INFLUENCE OF CAPITAL ADEQUACY RATIO (CAR), COMPANY SIZE, LIQUIDITY ON FINANCIAL PERFORMANCE AND QUALITY OF THE SHARIA BOARD AS MODERATION VARIABLES - Haribowo, Ismawati; Murwaningsari, Etty (KRISNA: Kumpulan Riset Akuntansi, 2025)
This study aims to examine the effect of Capital Adequacy Ratio, Company Size, Liquidity on Financial Performance and moderated by the Quality of the Sharia Board. This study uses secondary data. Sampling was carried out using the purposive sampling method. The number of samples in this study was 76 banks for the period 2020 - 2022. Analysis method For testing data processing in this study using multiple regression analysis and moderated regression analysis, using STATA. The results of this study indicate that CAR has an effect on Financial Performance. Meanwhile, company size and liquidity do not affect financial performance. Furthermore, the Quality of the Sharia Board can moderate the effect of CAR on Financial Performance.